Physical Activity among Middle-aged Adults After Total Hip Arthroplasty Following One Year: Physical Activity After Total Hip Arthroplasty - Waheed, Muhammad Waqas; Sadiq, Samreen; Hamid, Khizra; Miraan, Ahmad; Mushtaq, Zeeshan (Pakistan Journal of Health Sciences, 2025)
Total hip arthroplasty is one of the common surgical procedures that is used to treat the diseases of the hip joint and improve mobility and physical activity. Evaluating the physical after total hip arthroplasty is critical to understanding recovery and outcomes for long-term effectiveness. Objective: To evaluate physical Activity after total hip arthroplasty following one Year. Methods: The questionnaire-based descriptive case series included 50 subjects (27 Male and 23 Female) after total hip arthroplasty. The sample size was collected using the WHO calculator. Physical Activity and pain were evaluated using the Harris Hip Score. The data were analyzed using SPSS version 20. Results: Middle-aged patients aged 55-65 years were evaluated using the Harris Hip Score. Physical Activity was gradually fair to good in patients with total hip arthroplasty following one Year. In 50 patients of THA, the grades of total Harris hip score were with 14 patients (28%) in Poor grade (˂70), 17 patients (34%) in Fair grade (70-79), 18 patients (36%) in Good grade (80-89) and one patient (2%) in Excellent grade (90-100). Conclusions: It was concluded that the majority of middle-aged adults, after total hip arthroplasty, presented with fair to good (34 % & 36 %) physical activity following one Year.